Emoji as a tool to aid the comprehension of written sarcasm: Evidence from younger and older adults. (January 2022) - Garcia, Charlotte; Țurcan, Alexandra; Howman, Hannah; Filik, Ruth
Abstract: There is evidence for an age-related decline in the ability to understand non-literal language such as sarcasm. There is also evidence to suggest that devices such as emoticons/emojis may influence sarcasm comprehension in younger adults. However, research examining whether such devices may improve written sarcasm comprehension in older adults is scarce. The present study used an online rating task to investigate the influence of the winking face emoji on both the interpretation and perception of message intent for sarcastic or literal criticism or praise. Results revealed that older adults, in comparison to their younger counterparts, demonstrated deficient ability in interpreting and perceiving sarcastic intent. However, older adults' interpretation and perception of sarcastic intent were significantly improved when the messages were accompanied by the winking face emoji. This would suggest that the winking face emoji is a clear indicator of sarcastic intent, compensating for the absence of non-verbal cues in written communication, and may play a useful role in successful intergenerational communication. Highlights: Older adults experience difficulty interpreting sarcasm in on-line communication. Emojis can aid sarcasm interpretation in both younger and older adults. Emojis can be a useful tool in facilitating successful intergenerational communication.